2007
DOI: 10.1186/1467-4866-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Microbial sulfate reduction and metal attenuation in pH 4 acid mine water

Abstract: Sediments recovered from the flooded mine workings of the Penn Mine, a Cu-Zn mine abandoned since the early 1960s, were cultured for anaerobic bacteria over a range of pH (4.0 to 7.5). The molecular biology of sediments and cultures was studied to determine whether sulfate-reducing bacteria (SRB) were active in moderately acidic conditions present in the underground mine workings. Here we document multiple, independent analyses and show evidence that sulfate reduction and associated metal attenuation are occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 67 publications
7
58
0
1
Order By: Relevance
“…However, studies on the environmental impact by coal mining are relatively recent in Brazil (Teixeira et al 2000, Pampêo et al 2004. Special attention has been given to acid drainage remediation (Fungaro and Izidoro 2006, Soares et al 2006, Church et al 2007), but few studies have focused on the regional characterization of water systems and AMD influence on their physico-chemical conditions. The main objective of this study was to evaluate the possible influence of the acid drainage coming from a mining area within the Figueira region on the quality of surface and ground waters particularly in relation to metals and As.…”
mentioning
confidence: 99%
“…However, studies on the environmental impact by coal mining are relatively recent in Brazil (Teixeira et al 2000, Pampêo et al 2004. Special attention has been given to acid drainage remediation (Fungaro and Izidoro 2006, Soares et al 2006, Church et al 2007), but few studies have focused on the regional characterization of water systems and AMD influence on their physico-chemical conditions. The main objective of this study was to evaluate the possible influence of the acid drainage coming from a mining area within the Figueira region on the quality of surface and ground waters particularly in relation to metals and As.…”
mentioning
confidence: 99%
“…In AMD systems, sulphate reduction to sulphide occurs at a pH of between 2 and 3 (Koschorreck et al 2003). Nevertheless, Church et al (2007) show sulphate reduction at a pH of between 4.0 and 7.5 when catalysed by anaerobic bacteria. Additionally, the anoxic conditions in the hypolimnion are associated with an increase in Fe and Mn concentrations in this zone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SRB grow optimally under circum-neutral conditions, therefore the AMD treatment that is mediated by SRB requires pH neutralization. However, many researchers have studied acid-tolerant and acidophilic SRB [21,36,[37][38][39][40]. Kimura, et al [41] have reported a reduction of sulfate at pH 3.8, and Bijmans, et al [42] reported a high rate of sulfate reduction at pH 4.0 and 4.5 using H2 and formate as electron donors in laboratory experiments.…”
Section: Arsenic and Iron Are Removed In Sulfate Reduction Reactorsmentioning
confidence: 99%